PENGARUH IMPLEMENTASI SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN BAGIAN UMUM SEKRETARIAT DAERAH KOTA BATU - Firdaus, Rizalnur; Yarzuqu, Asya; Dolaksaribu, Tio Ariella (Fakultas Ekonomi Universitas Kadiri, 2025)
The quality of financial reports is essential to ensuring accountability and transparency in regional financial management. This study examines the partial influence of the Regional Government Information System (SIPD) implementation and information technology on the quality of financial reports. The research was conducted in the General Affairs Division of the Regional Secretariat of Batu City using a quantitative approach. A purposive sampling method was applied, with 45 respondents selected. Data were analyzed using IBM SPSS Statistics 25. The results show that SIPD implementation has a positive but not statistically significant effect on financial report quality, indicating suboptimal use, possibly due to technical constraints such as system instability or slowness. In contrast, information technology use has a positive and significant effect. These findings suggest that information technology plays a more dominant role in enhancing the quality of financial reporting in the studied context